Brazil Essays on History and Politics - Bethell, Leslie (University of London Press, 2018)
Published to mark his 80th birthday, this volume consists of seven essays by Leslie Bethell on major themes in modern Brazilian history and politics: Brazil and Latin America; Britain and Brazil (1808-1914); The Paraguayan War (1864-70); The decline and fall of slavery (1850-1888); The long road to democracy; Populism; The failure of the Left. The essays are new, but they draw on book chapters and journal articles published (mainly in Portuguese) and public lectures delivered in the ten years since his retirement as founding Director of the University of Oxford Centre for Brazilian Studies in 2007. In an autobiographical Introduction (Why Brazil?) Professor Bethell describes how, from the most unlikely of backgrounds, he became a historian of Brazil and how he came to devote much of his long academic career to the promotion and development of Brazilian studies in UK (and, to a lesser extent, US) universities.